2020
DOI: 10.1007/s00167-020-06193-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgery improves the clinical and radiological outcome in Rockwood type IV dislocations, whereas Rockwood type III dislocations benefit from conservative treatment

Abstract: Purpose Despite the available classiications, diagnostics and treatment of acute acromioclavicular joint (ACJ) injuries are still vague and challenging for trauma and shoulder surgeons. This study aimed to evaluate the dynamic radiographic as well as clinical outcome of operatively and conservatively treated Rockwood (RW) type III and IV ACJ dislocations. All patients with RW type III and IV ACJ dislocations between 2009 and 2016 (n = 226) were included in this retrospective data analysis with a prospective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In accordance, previous studies in the literature reported postoperative ASES scores ranging from 82% to 98% after an arthroscopically assisted technique employing suspensory fixation systems. 3 , 4 , 10 , 11 , 13 The difference noted in this study between SANE scores of isolated C-stabilization and combined CC stabilization and AC cerclage across the study population ( Table 1 ) and VAS rest scores in the non-flat subtype ( Table 3 ) that reach statistical significance do not reach the minimal clinically important difference and are thus not regarded clinically relevant. 25 …”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In accordance, previous studies in the literature reported postoperative ASES scores ranging from 82% to 98% after an arthroscopically assisted technique employing suspensory fixation systems. 3 , 4 , 10 , 11 , 13 The difference noted in this study between SANE scores of isolated C-stabilization and combined CC stabilization and AC cerclage across the study population ( Table 1 ) and VAS rest scores in the non-flat subtype ( Table 3 ) that reach statistical significance do not reach the minimal clinically important difference and are thus not regarded clinically relevant. 25 …”
Section: Discussionmentioning
confidence: 68%
“… 1 There exists a general consensus throughout the literature that acromioclavicular joint injuries (ACJI) Rockwood type I, II, and IIIA can be managed nonoperatively, whereas ACJI Rockwood type IIIB and IV-VI dislocations should be treated surgically. 2 , 3 , 4 , 5 Surgical management with arthroscopically assisted suspensory fixation for coracoclavicular stabilization may result in favorable outcomes. 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acromioclavicular (AC) joint injuries account for a significant proportion of shoulder injuries, especially in athletes engaging in contact sports [ 1 , 4 , 14 , 27 , 30 , 36 ]. While current literature supports a non-operative management of low-grade AC joint injuries, Rockwood type IIIB and IV-VI dislocations should generally be treated surgically [ 1 , 13 , 29 , 31 ]. With recent literature covering a wide range of open and arthroscopic procedures, a growing body of evidence reports the arthroscopically assisted technique employing suspensory fixation systems to reliably achieve favorable clinical outcomes [ 10 , 13 , 22 , 29 , 37 , 38 , 41 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The AC joint dislocation can be classified according to Rockwood [9]. Most of the Rockwood type IV, V and VI AC joint injuries need to be reduced and stabilized surgically [1, 6, 7, 17]. For the surgical treatment of acute AC joint injuries, there is widespread consensus to perform an arthroscopic anatomic reconstruction with a suspensory device [18].…”
Section: Introductionmentioning
confidence: 99%